Rhizosphere Microbial Communities Are Significantly Affected by Optimized Phosphorus Management in a Slope Farming System - Deng, Qianxin; Zhang, Tong; Xie, Deti; Yang, Yuheng (Frontiers in Microbiology, 2021)
Soil rhizosphere microorganisms play a crucial role in promoting plant nutrient absorption and maintaining soil health. However, the effects of different phosphorus (P) managements on soil microbial communities are poorly understood in a slope farming system. Here, rhizosphere microbial communities under two P fertilization levels, conventional (125 kg P2O5 ha−1, P125) and optimal (90 kg P2O5 ha−1, P90), were compared at four growth stages of maize in a typical sloped farming system. The richness and diversity of rhizosphere bacterial communities showed significant dynamic changes throughout the growth period of maize, while different results were observed in fungal communities. However, both P fertilization levels and growth stages influenced the structure and composition of the maize rhizosphere microbiota. Notably, compared to P125, Pseudomonas, Conexibacter, Mycobacterium, Acidothermus, Glomeromycota, and Talaromyces were significantly enriched in different growth stages of maize under P90, while the relative abundance of Fusarium was significantly decreased during the maize harvest. Soil total nitrogen (TN) and pH are the first environmental drivers for changing in bacterial and fungal community structures, respectively. The abundance of Gemmatimonadota, Proteobacteria, and Cyanobacteria showed significant correlation with soil TN, while that of Basidiomycota and Mortierellomycota were significantly related to pH. Additionally, P90 strengthened the connection between bacteria, while reduced the links between fungi at the genus level. Our work helps to understand the role of P fertilization levels in shaping the rhizosphere microbiota and may manipulate beneficial microorganisms for better P use efficiency.